Reciprocal Associations between Boys’ Externalizing Problems and Mothers’ Depressive Symptoms - Gross, Heather E. (2008)
Although much has been written about the utility of applying transactional models to the study of parenting practices, relatively few researchers have used such an approach to examine how children influence maternal wellbeing throughout their development. Using a sample of males from predominantly low-income families, the current study explored reciprocal relations between boys’ overt disruptive behavior (boys’ ages 5 to 10 years) and maternal depressive symptoms. We then examined this model with youth-reported antisocial behaviors (ASB) and maternal depressive symptoms when the boys were older, ages 10 to 15. In middle childhood, evidence was found for both maternal and child effects from boys’ ages 5 to 6 using both maternal and alternative caregiver report of child aggressive behavior. In the early adolescence model, consistent maternal effects were found, and child effects were evident during the transition to adolescence (boys’ ages 11 to 12). The findings are discussed in reference to reciprocal models of child development and prevention efforts to reduce both maternal depression and the prevalence of child antisocial behavior.